Evaluation of multiple access strategies for multimedia communications in indoor wireless networks - Bing, Benny Kheng Teck. (2010)
Growing emphasis on multimedia applications in wireless networks calls for the development of multiple access protocols capable of supporting demanding applications such as audio/video playback, image browsing, real-time voice/video transmission and interactive data exchange in a unified manner. Current multiple access strategies are generally inadequate in addressing the combined requirements of wireless and multimedia communications where channel characteristics and traffic load distributions change dynamically with time. In addition, the channel access protocol needs to be designed such that users share the limited communications bandwidth efficiently. This implies two criteria : maximizing the utilization of the radio frequency spectrum and minimizing the delay experienced by the users.